Political and social protests from the margins: the role of Mizrahi Jews in Israeli grassroots activism - Daniele, G. (Etnográfica, 2019)
This paper deals with the role of the most marginalized communities in social and political grassroots activism inside Israel, by focussing on the demanding issue that affects the combination of asymmetric relationships, internal discriminations and increasing inequalities within political protests. In detail, I analyse the involvement of social and political activists struggling to improve the rights of and in solidarity with Mizrahi Jews who have experienced different kinds of discrimination in Israeli society, but also in a few Israeli peace-oriented and leftist contexts. Such heterogeneity of Israeli Jewish political and social grassroots organisations and the crucial role of Mizrahi Jewish activists can be considered as a challenging field of study needing to be analysed and related to the main subject matters concerning the Israeli current status quo.